Pemanfaatan Sumber Daya Genetik Lokal dalam Perakitan Varietas Unggul Cabai (Capsicum annuum) Tahan Terhadap Penyakit Antraknosa yang Disebabkan oleh Colletotrichum sp - Muhamad Syukur; Rahmi Yunianti; . Rustam; . Widodo (Institut Pertanian Bogor, 2013)
The use of resistant varieties based on local resources is one way to solve the problem of anthracnose disease. This study aims to identify the species of anthracnose isolates (Colletotricum accutatum, C. gloeosporioides, and C. capsici) from the various centers of chili production through the characterization of conidia, get the genotypes that are resistant to anthracnose disease, and get information about resistance to anthracnose disease of chili pepper lines. Research activities include morphological characterization of Colletotrichum isolates, screening of resistance the chili pepper lines to anthracnose disease, and screening of resistance the pepper genotypes of exploration results to anthracnose disease. The results showed that the isolates found in the field consist of 3 species, namely C. capsici, C. acutatum, and C. gloesporioides. Forty two isolates of 67 isolates were C. capsici, the rest were C. acutatum or C. gloesporioides. The chili pepper lines were tested, including the criteria for moderate to highly susceptible to anthracnose diseases caused by C. acutatum. IPB C15 Genotype was consistently more resistant to anthracnose caused by C. acutatum as compared to 27 other genotypes.